Sexual harassment in the workplace : a gendered inequality - Malatjie, Khomotso Rosina (My University, 2022)
Sexual harassment remains an issue in the workplace as result of ineffective legislative and other measures that fail to recognise sexual harassment as a form of discrimination that is gender orientated. Gender inequality is credited as one of the contributors of sexual harassment, as more women than men suffer sexual harassment in the workplace. Moreover, sexual harassment has adverse effects on the individual who is on the receiving end of it, which are psychological in nature. This alone may lead to the abuse of substances as a form of coping mechanism, to arriving late to work or quitting which also affects productivity. In an attempt to confront the issue of sexual harassment, laws were created over the years, both at national and international level. Although some countries show efficiency in the creation of these laws by responding with urgency, some countries have had a more difficult time formulating appropriate and effective laws, with some countries having very little laws aimed at combatting sexual harassment in the workplace. At the same time workplace sexual harassment policies have proven to be an effective weapon against the gendered inequality that is sexual harassment if implemented effectively.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2022
Keywords: Discrimination; Gender inequality; Hostile environment; Quid pro quo; Sexual harassment; Sexual harassment of women -- South Africa; Sexual discrimination; Sex discrimination in employment